Mineral natural table waters as a component of sanatorium-resort children rehabilitation complexes in the remission of oncological diseases - A. A. Shapovalova; K. D. Babov; N. S. Badiuk (Kazimierz Wielki University, 2017)
Urgency. High rates of oncological diseases (11.5-12.0 per 10.000 of children's population) dictate the need for comprehensive approaches to the organization of the rehabilitation process. The objective: to justify the advisability of using mineral natural table water in the period of oncopathology remission in children under conditions of sanatorium-and-spa rehabilitation. Materials and methods. The algorithm of the children's examination included the study of anamnesis, complaints, initial nonspecific adaptive-adaptation reactions (according to the general clinical analysis of blood). The general rehabilitation complex (GRC) included a dose-sparing motion regimen; climatotherapy, diet food, therapeutic exercises in special medical groups, singlet-oxygen cocktail, phytotea (holosas with ascorbic acid), psychological support. In addition to GRC in 2 therapeutic complexes (TC) mineral natural table waters (MW) Truskavetskaya Akva-Eko mineral water (TC1 after treatment of solid tumors) and Morshinskaya (TC2 after treatment of oncohematological diseases). Results. The general tendency to the mend of sick children state under the influence of TC1 was established in comparison with GRC. It manifested in significant changes of various levels (P